2015
DOI: 10.1093/sysbio/syv070
|View full text |Cite
|
Sign up to set email alerts
|

Rumbling Orchids: How To Assess Divergent Evolution Between Chloroplast Endosymbionts and the Nuclear Host

Abstract: Phylogenetic relationships inferred from multilocus organellar and nuclear DNA data are often difficult to resolve because of evolutionary conflicts among gene trees. However, conflicting or "outlier" associations (i.e., linked pairs of "operational terminal units" in two phylogenies) among these data sets often provide valuable information on evolutionary processes such as chloroplast capture following hybridization, incomplete lineage sorting, and horizontal gene transfer. Statistical tools that to date have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 67 publications
2
69
0
3
Order By: Relevance
“…The issue of more than one version of trnL-trnF in these orchids deserves further research, which is beyond the scope of this study. Phylogenetic analyses:-Both the MP and BI analyses of all datasets recovered Mormodes as monophyletic, in agreement with previous morphological (Romero-González 1990, Chase & Hills 1992) and molecular studies (Pridgeon & Chase 1998, Salazar et al 2009, Pérez-Escobar et al 2015. Both analyses also support monophyly of section Coryodes (BP 90, PP 0.84, respectively), but section Mormodes received low support from the MP analysis (BP 70) and was not recovered as monophyletic in the BI analysis (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…The issue of more than one version of trnL-trnF in these orchids deserves further research, which is beyond the scope of this study. Phylogenetic analyses:-Both the MP and BI analyses of all datasets recovered Mormodes as monophyletic, in agreement with previous morphological (Romero-González 1990, Chase & Hills 1992) and molecular studies (Pridgeon & Chase 1998, Salazar et al 2009, Pérez-Escobar et al 2015. Both analyses also support monophyly of section Coryodes (BP 90, PP 0.84, respectively), but section Mormodes received low support from the MP analysis (BP 70) and was not recovered as monophyletic in the BI analysis (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…Previous phylogenetic studies about Catasetinae have included not more than three species of Cycnoches 47, 48, 50, 51, 55 , hence keeping internal relationships (and corresponding conflicts, see below) of the lineages unresolved. Serious phylogenetic incongruence between nuclear and plastid tree topologies of Catasetinae has been firstly identified by Pérez-Escobar and colleagues 64 , but the plausibility of the trees were not discussed before.…”
Section: Discussionmentioning
confidence: 99%
“…We also sequenced a ~1500 bp fragment of the plastid gene ycf 1, as well as the trn S– trn G intergenic spacer. Amplification and sequencing settings, as well as sequencing primers used for ITS, ETS, Xdh , trn S– trn G, and ycf 1, are the same as previously reported 64, 81 (Tab. S2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have used nuclear simple sequence repeat (SSR) chloroplast DNA makers to study phylogeny and population variation [2,3]. Previously, studies found a conflict (inconsistency) between the phylogeny of plastid data and nuclear data in Senecioneae and Neotropical Catasetinae [4,5]. Therefore, it is not sufficient to study Quercus simply by using plastid regions.…”
Section: Introductionmentioning
confidence: 99%